2001
DOI: 10.1086/321639
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Mass during Low‐Mass Star Formation. II. Modeling the Submillimeter Emission from Preprotostellar Cores

Abstract: We have modeled the emission from dust in pre-protostellar cores, including a self-consistent calculation of the temperature distribution for each input density distribution. Model density distributions include Bonnor-Ebert spheres and power laws. The Bonnor-Ebert spheres fit the data well for all three cores we have modeled. The dust temperatures decline to very low values (T d ∼ 7 K) in the centers of these cores, strongly affecting the dust emission. Compared to earlier models that assume constant dust temp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

70
484
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(557 citation statements)
references
References 44 publications
70
484
3
Order By: Relevance
“…In non-embedded cores, the dust temperature drops from around 17 K at the edge of the core to 7 K at the centre of the core, as previous studies have already indicated (Zucconi et al 2001;Evans et al 2001;Stamatellos & Whitworth 2003a). We also find that the dust temperature inside cores with disk-like asymmetry is θ dependent (see Fig.…”
Section: Results: Core Temperatures Seds and Imagessupporting
confidence: 78%
See 1 more Smart Citation
“…In non-embedded cores, the dust temperature drops from around 17 K at the edge of the core to 7 K at the centre of the core, as previous studies have already indicated (Zucconi et al 2001;Evans et al 2001;Stamatellos & Whitworth 2003a). We also find that the dust temperature inside cores with disk-like asymmetry is θ dependent (see Fig.…”
Section: Results: Core Temperatures Seds and Imagessupporting
confidence: 78%
“…Previous continuum radiative transfer modelling of prestellar cores has examined non-embedded BE spheres (Evans et al 2001;Young et al 2003) and embedded BE spheres (Stamatellos & Whitworth 2003a), using 1D (sphericallysymmetric) codes. Zucconi et al (2001) have used an approximate, semi-analytic method to model non-embedded, magnetically flattened prestellar cores, in 2D.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we show that the pinching of the magnetic field expected in dense, self-gravitating molecular cloud cores naturally produces a decrease of the polarization degree toward the centre of the core, for a large range of viewing angles. In addition, we find that this geometrical depolarization effect is further enhanced by a dust temperature gradient increasing outward, as expected in externally heated starless cores (Evans et al 2001;Zucconi et al 2001;Stamatellos & Whitworth 2003;Gonçalves et al 2004, hereafter GGW). However, while these effects can contribute substantially to the observed depolarization, the measured p−I relations are sometimes steeper than our predictions.…”
Section: L1544supporting
confidence: 83%
“…Such a correlation might be expected based on a model in which the dust is heated by the interstellar radiation field (ISRF). Large column densities then provide more shielding, resulting in cooler dust (Evans et al 2001;Stamatellos et al 2007;Roy et al 2014). But could this correlation be an artifact, induced by a degeneracy between mass and temperature in the SED measurement model?…”
Section: Estimates Of Core Masses and Temperaturesmentioning
confidence: 99%